Hybrid active damping of LCL-filtered grid connected converter - Ghanem, A.; Rashed, Mohamed; Sumner, M.; Elsayes, M.A.; Mansy, I.I.I. (2016)
A method for hybrid active damping in power converters connected to a weak grid using an LCL filter is proposed. It uses feedback of the grid current and capacitor voltage and is derived as an equivalent to the capacitor current feedback active damping method. A co-design procedure for the grid current controller with the proposed hybrid active damping method is presented. The robustness, system bandwidth and harmonic rejection are studied. The proposed method is applied to a single grid connected converter with variable grid inductance to investigate its ability to damp different system resonance frequencies and its effectiveness is verified via frequency domain analysis and time domain simulation.